Spectroscopic and photometric oscillatory envelope variability during the S Doradus outburst of the luminous blue variable R71 - Mehner, Andrea; Stahl, Otmar (Astronomy and astrophysics, 2017)
Context. Luminous blue variables (LBVs) are evolved massive stars that exhibit instabilities that are not yet understood. Stars can lose several solar masses during this evolutionary phase. The LBV phenomenon is thus critical to our understanding of the evolution of the most massive stars.Aims. The LBV R71 in the Large Magellanic Cloud is presently undergoing an S Doradus outburst, which started in 2005. To better understand the LBV phenomenon, we determine the fundamental stellar parameters of R71 during its quiescence phase. In addition, we analyze multiwavelength spectra and photometry obtained during the current outburst.Methods. We analyzed pre-outburst CASPEC spectra from 1984-1997, EMMI spectra in 2000, UVES spectra in 2002, and FEROS spectra from 2005 with the radiative transfer code CMFGEN to determine the fundamental stellar parameters of the star. A spectroscopic monitoring program with VLT X-shooter since 2012 secured visual to near-infrared spectra throughout the current outburst, which is well-covered by ASAS and AAVSO photometry. Mid-infrared images and radio data were also obtained.Results. During quiescence, R71 has an effective temperature of Teff = 15 500 K and a luminosity of log(L∗/L⊙) = 5.78. We determine its mass-loss rate to 4.0 × 10-6M⊙ yr-1. We present the spectral energy distribution of R71 from the near-ultraviolet to the mid-infrared during its present outburst. Semi-regular oscillatory variability in the light curve of the star is observed during the current outburst. Absorption lines develop a second blue component on a timescale of twice that length. The variability may consist of one (quasi-)periodic component with P ~ 425/850 d with additional variations superimposed.Conclusions. R71 is a classical LBV, but this star is at the lower luminosity end of this group. Mid-infrared observations suggest that we are witnessing dust formation and grain evolution. During its current S Doradus outburst, R71 occupies a region in the HR diagram at the high-luminosity extension of the Cepheid instability strip and exhibits similar irregular variations as RV Tau variables. LBVs do not pass the Cepheid instability strip because of core evolution, but they develop comparable cool, low-mass, extended atmospheres in which convective instabilities may occur. As in the case of RV Tau variables, the occurrence of double absorption lines with an apparent regular cycle may be due to shocks within the atmosphere and period doubling may explain the factor of two in the lengths of the photometric and spectroscopic cycles.